Pengembangan Usaha Industri Jamu dan Minuman PD Budi Lestari di Jakarta - Tanjung Prasetyo; Daniel R. Monintja; Fransiska Rungkat Zakaria (Institut Pertanian Bogor, 2009)
The aim of this study is to identity successful business conducts carried out by the company. The successful business conducts identified are: (1) Employing skillful marketing personnel, (2) Having a wide marketing channels, (3) Application of production contract, (4) Utilizing brokers in marketing the product, (5) Utilizing secondhand containers to reduce cost.The method used from this study is SWOT analysis with primary and secondary data, which are collected through literature and interview.Based on the results of the SWOT analysis, there were some suggestions to PD. Budi Lestari in order to develop its business by : (1) Increasing working capital, (2) Increasing the quality of human resources, (3) Making promotions, (4) Increasing the machine technologies utilizing, (5) Finding new bottles using altenatives in solving problem of getting used bottles, (6) Using labels that includes the special qualities of the drinks to explain the characteristic and quality from each product made, (7) Selecting the distribution of used bottles facilities.Beside that, suggestions given from this study can be an input to the company in raising its sales volume as an effort to fulfill market’s demand, includes mini and super markets.